2004
DOI: 10.1124/jpet.104.068254
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipocyte Fatty Acid-Binding Protein (aP2) Gene Promoter-Driven Reporter Assay Discriminates Nonlipogenic Peroxisome Proliferator-Activated Receptor γ Ligands

Abstract: Peroxisome proliferator-activated receptors (PPARs) regulate storage and catabolism of fats and carbohydrates. PPAR␥ activity increases insulin sensitivity and adipocyte differentiation at the expense of adipogenesis and weight gain. The goal of this study was to 1) clone the promoter of the human adipocyte fatty acid binding protein (aP2) gene, namely fatty acid-binding protein-4, 2) characterize its pharmacological regulation, and 3) determine its putative predictability for adipogenesis. Among the selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 35 publications
(42 reference statements)
0
28
1
Order By: Relevance
“…FABP4 facilitates transport of fatty acid ligands to the nucleus, 35,36 where it interacts directly with PPAR␥. 37,38 Various data support the concept that FABP4 is at the crossroads of 2 central pathways in macrophages, where it coordinates cholesterol metabolism and inflammatory response. 39 In mice, it appears that FABP4 is required for expression of inflammatory cytokines and/or chemoattractants in macrophages and adipose tissue.…”
Section: Sarov-blat Et Al Inflammation In Macrophages Of Low Hdl Subjmentioning
confidence: 92%
“…FABP4 facilitates transport of fatty acid ligands to the nucleus, 35,36 where it interacts directly with PPAR␥. 37,38 Various data support the concept that FABP4 is at the crossroads of 2 central pathways in macrophages, where it coordinates cholesterol metabolism and inflammatory response. 39 In mice, it appears that FABP4 is required for expression of inflammatory cytokines and/or chemoattractants in macrophages and adipose tissue.…”
Section: Sarov-blat Et Al Inflammation In Macrophages Of Low Hdl Subjmentioning
confidence: 92%
“…Sequence analysis showed that there was no PPRE-like motif in human A-FABP promoter. 40 Rival et al 41 all the same have characterized a functional promoter of the human A-FABP gene and showed that rosiglitazone and pioglitazone displayed a high efficacy on reporter-gene assays in COS-7 cells cotransfected by a human A-FABP promoter-based Luc reporter vector and fulllength human PPAR expression plasmids. Surprisingly, in these experiments, a selective PPARa agonist (BM-17.1744) did not stimulate the human A-FABP-PPARa promoter reporter-gene assay.…”
Section: Discussionmentioning
confidence: 99%
“…GRO-seq (Core et al 2008;Wang et al 2011) was used to measure nascent gene transcription in mouse 3T3-L1 adipocytes and after treatment with rosi for 10 min, 30 min, 1 h, and 3 h. The Fabp4 locus, a classic adipocyte PPARg gene target (Spiegelman and Green 1980;Rival et al 2004), showed increased transcription with rosi treatment (Fig. 1A).…”
Section: Rosi Rapidly and Robustly Regulates Gene Transcription In Admentioning
confidence: 99%